STUDI PERILAKU MONYET EKOR PANJANG (Macaca fascicularis) DI KAWASAN KAMPUS UNJA MENDALO - Aditiya, Randi; Meitriani, Yohana; Saragih, Rasmita Berliana; Angelita, Antra; Hanum, Nabila Asri; Ramadhona, Octory Fillia; Hombing, Apriana Br; Adriadi, Ade; Suprayogi, Dawam (BIOMA : JURNAL BIOLOGI MAKASSAR, 2026)
This study aims to explain the daily activity patterns of long-tailed monkeys (Macaca fascicularis) in the area of ​​the University of Jambi (UNJA) Mendalo Campus. This study was conducted using a descriptive quantitative approach through the focal animal sampling method in four main locations (UNJA Jami' Mosque, UNJA Lake, UNJA LPTIK, and UNJA FKIP). The research location was determined by purposive sampling, namely in areas inhabited by long-tailed monkey populations, at three different times (morning, afternoon, evening). In each location, one individual monkey was observed for 1 hour per period with behavioral recording every 5 minutes. The results of the study showed that the most common behaviors were eating, moving, and grooming, with activity patterns varying in each location and time. Locations that have open food sources, such as UNJA Jami' Mosque, tend to be the focus for eating and grooming activities, while quieter locations such as UNJA Lake and LPTIK support playing and grooming activities. Environmental factors, such as food availability and the level of human disturbance, have a significant impact on monkey activity patterns. The results of this study are expected to be a basis for managing a campus environment that is balanced between human activities and the existence of wildlife. Keywords : Macaca fascicularis, Daily behavior, Behavioral ecology, Jambi University campus, Focal animal sampling, Semi-urban environment